Experimental and numerical study on the lateral torsional buckling of full-scale steel-timber composite beams. Issue 3 (February 2022) - Gao, Ying; Xu, Feiyang; Meng, Xinmiao; Zhang, Ye; Yang, Hongda
The lateral torsional buckling (LTB) of steel-timber composite (STC) beam with partial interaction was investigated in this paper. The composite beam is constructed by connecting the timber to both flanges of the H-shaped steel with bolts or screws. Twelve push-out specimens were designed to evaluate the shear performance of bolt or screw connectors. It was shown that the slip stiffness and the shear bearing capacity of the connectors increased with the thickness of timber increasing. Then, eight full-scale composite beams with lengths of 6000 mm were studied through bending tests and compared to a bare steel beam. The experimental behaviors of the specimens were identified, including the failure mode, load-deflection relationship and load-strain response. The LTB phenomenon and composite action were discussed by analyzing the strain distribution, stiffness and strength. The results demonstrated that the STC beams fastened with bolts or screws displayed partial composite action. Although the stiffness of the composite beam showed little augmentation, the maximum strength of the composite beam substantially increased by suppressing the LTB phenomenon. A finite element analysis was conducted to reveal the failure mechanism of the specimens with different geometric and physical parameters, including the number of timber layers, the interface shear stiffness and the initial imperfection. It was found that increasing the number of timber layers in the upper flange suppressed the lateral torsional buckling, and the interface shear stiffness was the key factor to control the stiffness and failure modes of STC beams.